PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN MODEL SIKLUS BELAJAR HIPOTETIK DEDUKTIF UNTUK MENINGKATKAN PENGUASAAN KONSEP SISWA PADA MATERI LARUTAN ASAM BASA DI SMA - Suryani, Wihdati; Suyatno, Suyatno; Erman, Erman (Universitas Negeri Surabaya, 2016)
This study purposed to produce a teaching materials with hypothetical deductive learning cycle model in the material acid solution decent base to improve the mastery of concepts. Development of the teaching materials using the Research & Development (R & D). The teaching materials developed consisting of lesson plan, student?s book, worksheets and test of concept mastery. The teaching materials were tested to the students of class XI SMA Muhammadiyah 5 Gresik in the first semester of the academic year 2015/2016. The design of trials using One Group Pre-test and Post-test Design. The results showed that (1) The validity of the teaching materials respectively acquire the criteria very valid; (2) Practicality teaching materials seen from feasibility study learning implementation lesson plan got practice criteria with an average of 3.48, legibility student?s book scored an average legibility level of 58% so that the legibility level appropriate teaching materials, student activity increased toward centered learning on students; and (3) the effectiveness of the teaching materials that consists of responses students received a positive response from the students so that students feel interested in learning process using hypothetical deductive learning cycle model, score improvement of students' concepts mastery, the average value of n-gain by 0.71 by category high. Based on the analysis of data and discussion is concluded that the learning device with hypothetical deductive learning cycle model feasible for use in learning process. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran dengan model siklus belajar hipotetik deduktif pada materi larutan asam basa yang layak untuk meningkatkan penguasaan konsep. Pengembangan perangkat pembelajaran ini menggunakan model Research &Development (R&D). Perangkat pembelajaran yang dikembangkan terdiri dari RPP, BAS, LKS, dan tes penguasaan konsep. Perangkat pembelajaran di uji cobakan terhadap siswa kelas XI SMA Muhammadiyah 5 Gresik pada semester ganjil tahun ajaran 2015/2016. Rancangan uji coba menggunakan One Group Pre-test and Post-test Design. Hasil penelitian menunjukkan bahwa (1) Validitas perangkat pembelajaran masing-masing memperoleh kriteria sangat valid/valid; (2) Kepraktisan perangkat pembelajaran dilihat dari keterlaksanaan RPP mendapat kriteria baik dengan rata-rata 3,48, keterbacaan BAS mendapat nilai rata-rata tingkat keterbacaan sebesar 58% sehingga tingkat keterbacaannya materi tepat untuk pembelajaran, aktivitas siswa mengalami peningkatan ke arah pembelajaran yang berpusat pada siswa; dan (3) keefektifan perangkat pembelajaran yang terdiri dari respon siswa mendapat respon positif dari siswa sehingga siswa merasa tertarik pada proses pembelajaran menggunakan model siklus belajar hipotetik deduktif, skor peningkatan penguasaan konsep siswa, rata-rata nilai n-gain sebesar 0,71 dengan kategori sedang. Berdasarkan hasil analisis data dan pembahasan diperoleh kesimpulan bahwa perangkat pembelajaran dengan model siklus belajar hipotetik deduktif layak digunakan dalam pembelajaran